The Role of Hybrid-Working in Improving Employees' Satisfaction, Perceived Productivity, and Organizations' Capabilities - Aprilina, Rizky; Martdianty, Fanny (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2023)
Objective: This study aims to identify the factors influencing employees' satisfaction and productivity in hybrid-working, such as reconciliation between professional and personal lives, flow experience, work flexibility, and organizational support. It also aims to analyze the effect of employees' satisfaction and perceived productivity on workers' intention to continue working hybrid in the future. Design/Methods/Approach: Data was gathered through an online questionnaire sent to potential participants. A total of 433 eligible respondents were collected for analysis. This study utilized Structural Equation Modelling (SEM) to examine the connections between reconciliation, flow experience, flexibility, organizational support, employee satisfaction, perceived productivity, and workers' intention to continue with hybrid work. Findings: Consistent with the hypotheses, reconciliation, flow experience, flexibility, and organizational support are positively and significantly associated with employee satisfaction and perceived productivity while working from home. Employee satisfaction and perceived productivity also positively and significantly influence workers' intention to continue with hybrid-work. Originality: This study combines motivating factors and factors that focus on the relationship between employees and organizations to develop the antecedents affecting satisfaction and productivity during work-from-home. The findings of this study contradict the previous research regarding the influence of productivity on workers' intention to continue with hybrid work. Both satisfaction and perceived productivity significantly affect workers' intention to work hybrid in the future. This implies that employees feel higher satisfaction and productivity when working from home, hence the inclination to continue this particular working method. Practical/Policy implication: Given the results, top management and HR professionals should consider, at the earliest possible, to start implementing hybrid-work in the organizations. The findings imply that employees intend to continue with hybrid-work because they feel higher satisfaction and perceived productivity while working from home. Also, organizations can observe what factors can improve employee satisfaction and perceived productivity while working hybrid and utilize that information to provide a better working environment for employees and organizations.